THE EFFECT OF FINANCIAL RATIOS ON PROFIT GROWTH AMONG MANUFACTURING COMPANIES - Hung, Albert Ernest; Viriany, Viriany (International Journal of Application on Economics and Business, 2023)
The aims of this study is to determine the impact of Net Profit Margin, Debt-to-Equity Ratio, Total Asset Turnover, and Quick Ratio on profit growth in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. With predetermined criteria, 18 companies registered in the Indonesia Stock Exchange are obtained by using purposive sampling method. The analysis technique used is multiple linear regression analysis. This study found that Net Profit Margin, Debt-to-Equity Ratio, Total Asset Turnover, and Quick Ratio simultaneously affect profit growth. Partially, Profit growth is not affected by Net Profit Margin, Debt-to-Equity Ratio and Total Asset Turnover. Whereas Profit Growth is affected negatively by Quick Ratio.